PROVISION OF SAHARA SAVINGS BONUSES AT BANK ACEH SYARIAH BANDA ACEH BRANCH - Afriola, Nabila; Kurniawan, Cecep Sholeh (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2023)
The purpose of this thesis or research is to find out the legal application of the Wadi'ah Yad Dhamanah bonus contract on Bank Aceh Syariah Sahara Savings and the obstacle factors in the implementation of the Wadi'ah Yad Dhamanah contract on the Sahara Savings. This research is a qualitative study with a statude approach, historical approach and conceptual approach which is descriptive in nature. Data obtained from observations and interviews. The results showed that, the application of the law of giving bonuses to the Wadi'ah Yad Dhamanah contract on Sahara Savings at PT Bank Aceh Syariah Banda Aceh Branch based on the data obtained and its implementation refers to the Fatwa of the National Sharia Council, the provision of bonuses is also based on the bank system, namely ALCO (Asset Liabililty Committee). As for the obstacle factors in its implementation in terms of products, there are no obstacles, but obstacles to customer understanding regarding the provisions of the contract used and also related to the adequacy of deposits to get a Hajj seat so that it affects the schedule for Hajj departure. From the above explanation, it can be concluded that the provision of bonuses can be done provided that it must be in accordance with the Fatwa DSN-MUI and other laws and regulations, so as not to cause problems in its implementation.